Methodical Principles of Physical Education - Buranov Ilkhomjon Komilovich (International Journal of Scientific Trends, 2024)
The article discusses the methodological principles of physical education, which play a key role in teaching and developing the physical qualities of students. Principles such as accessibility, systematicity, consistency and individualization are described. Their application in pedagogical practice and their impact on the effectiveness of physical education are also analyzed.